Performance evaluation of a low-cost, novel vanadium nitride xerogel (VNXG) as a platinum-free electrocatalyst for dye-sensitized solar cells - Gnanasekar, Subashini; Sonar, Prashant; Jain, Sagar M.; Jeong, Soon Kwan; Grace, Andrews Nirmala (Royal Society of Chemistry, 2020)
A vanadium nitride xerogel (VNXG) was synthesised by a simple and effective method of ammonialising a vanadium pentoxide xerogel at a higher temperature. Xerogel-structured materials possess salient features such as high surface area, tunable porosity and pore size that result in enhancing the catalytic activity by a fast electron-transport pathway and increase electrolyte diffusion channels. Metal nitrides are reported as promising alternate low-cost counter electrodes to replace the conventional and expensive platinum (Pt) counter electrode. Though few studies are reported on aerogel-based CEs for DSSCs, the present work is the first attempt to synthesize and evaluate the performance of xerogel-structured metal nitrides as counter electrode materials for dye-sensitized solar cells. The synthesized material was well characterized for its structural and morphological characteristics and chemical constituents by photoelectron spectroscopy. Finally, the VNXG was tested for its electrocatalytic performance as a choice of counter electrodes for dye-sensitized solar cells (DSSCs). The photo-current studies were performed under standard 1 SUN, class AAA-simulated illumination with AM1.5G. The consolidated results revealed that the vanadium nitride xerogel exhibited good photocatalytic activity and low charge transfer resistance. This identified it as a promising low-cost counter electrode (CE) material for dye-sensitized solar cells. The photo-current conversion efficiency of the vanadium nitride xerogel CE-based DSSC reached 5.94% comparable to that of the conventional thermal decomposed Pt CE-based DSSC, 7.38% with the same iodide/triiodide electrolyte system. Moreover, the 28 days stability study of VNXG CE DSSCs provided an appreciably stable performance with 37% decrement in the PCE under the same test condition.